2021
DOI: 10.1111/lam.13494
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ciprofloxacin impurities on bacterial growth, antibiotic resistance development and content assays

Abstract: Significance and Impact of the Study: Increased evidence suggests that substandard antibiotics, which fail to meet quality standards and specifications and are prevalent in low-and middle-income countries, promote antibiotic resistance. How increased antibiotic impurities impact bacterial growth and antibiotic resistance is poorly characterized. Ciprofloxacin impurities (including a major photodegradation product) displayed modest antimicrobial activity against Escherichia coli. This can alter total activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…7 Regarding the assay results, underdosed antibiotics could be responsible for therapy failures and antibiotic resistance, which can lead to the reduction or absence of effectiveness of first-line therapies. 5,[35][36][37][38] The WHO has recently reported high resistance levels for Escherichia coli and Salmonella spp. to ciprofloxacin.…”
Section: Prevalence Of Sf Medicines and Cause Of Noncompliancementioning
confidence: 99%
“…7 Regarding the assay results, underdosed antibiotics could be responsible for therapy failures and antibiotic resistance, which can lead to the reduction or absence of effectiveness of first-line therapies. 5,[35][36][37][38] The WHO has recently reported high resistance levels for Escherichia coli and Salmonella spp. to ciprofloxacin.…”
Section: Prevalence Of Sf Medicines and Cause Of Noncompliancementioning
confidence: 99%
“…It underlines the need for more affordable medicine testing technologies, as well as greater attention to impurities and non-active ingredients in considering the quality of medicines. 5658…”
Section: Discussionmentioning
confidence: 99%
“…It underlines the need for more affordable medicine testing technologies, as well as greater attention to impurities and non-active ingredients in considering the quality of medicines. [56][57][58] Its limitations notwithstanding, our study remains one of the most comprehensive single-country academic surveys of medicine quality. And yet we underline that the field survey data imperfectly reflect the prevalence of out of specification products in the market, or their true threat to public health.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also shown that exposure to impurities and degradation products-unwanted chemicals or byproducts that can develop during the manufacturing, transportation, and storage of drugs-can promote AMR and interfere with content assays that aim to measure the quantity of API in a medicine. 15,16 Maintaining good storage and distribution practices along the medicines supply chain is also critical for maintaining quality medicines.…”
Section: Introductionmentioning
confidence: 99%